Revision of Terellia amberboae group of species (Diptera: Tephritidae) - Zarghani, Ebrahim; Khaghaninia, Samad; Namin, Saeed Mohamadzade; Korneyev, Valery A. (Zootaxa, 2017)
Terellia barughii new species from Tabriz (East Azerbaijan Province) and T. babaki new species from Qazvin Province (Iran) are described and figured, and Terellia amberboae V. Korneyev & Merz, 1996 is redescribed. A new species group is established, host plant and phylogenetic relationships are briefly discussed, and a key to species is provided.